Urban forests host rich polypore assemblages in a Nordic metropolitan area - Korhonen, Aku; Penttilä, Reijo; Siitonen, Juha; Miettinen, Otto; Immonen, Auli; Hamberg, Leena (Elsevier, 2021)
Urban forests are often remnants of former larger forested areas, and traditionally considered as degraded habitats due to negative effects of urbanization. However, recent studies have shown that urban forests managed for recreational purposes can be structurally close to natural forests and may provide habitat features, such as dead wood, that are scarce in intensively managed forest landscapes. In this study, we assessed how urbanization affects polypore species richness and the number of red-listed polypore species in forest stands, and the occurrences of polypore species on individual units of dead wood. Spruce-inhabiting polypore assemblages and their associations to urbanization, local habitat connectivity and dead-wood abundance were investigated in southern Finland. The effects of urbanization on polypore species richness and individual species were largely negligible when other environmental variability was accounted for. Several red-listed polypore species were found in dead-wood hotspots of urban forests, though urbanization had a marginally significant negative effect on their richness. The main driver of total species richness was dead-wood abundance while the number of red-listed species was also strongly dependent on local habitat connectivity, implying that a high degree of fragmentation can decrease their occurrence in urban forests. We conclude that the highest potential for providing habitats for threatened species in the urban context lies in large peri-urban recreational forests which have been preserved for recreational purposes around many cities. On the other hand, overall polypore diversity can be increased simply by increasing dead-wood abundance, irrespective of landscape context.
Keywords: Urban forest; Urban-rural gradient; Saproxylic; Dead wood; Coarse woody debris; Redlisted species